' people are going to want to know what really went down': Cloverfield and the return to innocence in post-9/11 America. Issue 1 (30th April 2012) - Overpeck, Deron
This article reads the American giant-monster film Cloverfield (Matt Reeves, 2008) as part of a national narcissistic response to the terrorist attacks in New York City in 2001 on September 11. Al Qaeda's deadly assault has been reconfigured from a geopolitical act of violence into an opportunity for an intrepid if callow young man to rescue his lost lover; the gigantic, rampaging creature and its city-wide battle with the military is almost a distraction to his quest. Inspired by Gojira (Inoshiro Honda, 1956), Cloverfield presents an unknowable, unpredictable, oft-unseen monster – the perfect villain for a horror film in the age of terrorism.